تأثير التلوث البصري على الصورة الدهنية والبيئة الحضرية للمدينة "شارع 17 فبراير (مركز مدينة الخمس) أنموذجاً" (Comprehensive Journal of Science, 2026)
Studying the visual composition of the urban area is important to achieve a good urban environment. In fact, visual pollution limits and weakens the formation of the mental image of the material components and urban spaces make the city unclear, witch distort the general appearance of the city. Kevin Lynch identified key elements for a clear image of the city, through which an impression of the city is drawn. This paper linked visual pollution and its effect on the quality of the clear image of the city. This paper then reviews Lynch's theory and the effect of visual distortion on mental image formation among city residents and visitors through an analytical study conducted on case study. The paper involving collecting, analyzing, and interpreting data to investigate basic elements for creating the mental image of the street and surveying the mental perception of residents and visitors about the area, and then identifying the shortcomings in drawing the mental image and drawing recommendations that could improve the mental image of the city.
Keywords: Urban Visual Pollution, Image of the city, Visual Urban city, Al-Komes city.